UNIVERSITY TEXTBOOK OF VOCAL AND INSTRUMENTAL TEACHING / MUSIC - Trtovac Dedeić, Alma H. (Metodička teorija i praksa, 2024)
The university textbook of vocal-instrumental teaching / music is an exceptional contribution to this topic, first of all due to its thorough coverage and the breadth of problem nodes covered, and then due to the fact that it was written by lecturers of academic institutions of national importance who in the true sense present modern methodical and didactic instructions through the technological improvement of music education. The mentioned textbook resulted from the long-term continuous pedagogical and performing practice of the authors Radmila Stojanović and Ozrenka Bjelobrk Babić and is a product of the reaction to the student needs of future teachers/educators as well as the needs in the educational and educational practice of professional teachers/educators.